PHYSICAL QUALITIES OF STUDENTS LEARN. - G.N. Ernazarov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article describes the results of pedagogical experiments conducted on the ability of students to quickly re-adapt to sudden changes in their movement activity during physical education classes and to improve their health and physical qualities.